2016
DOI: 10.1136/inp.i75
|View full text |Cite
|
Sign up to set email alerts
|

Equine back disorders 2. Treatment options

Abstract: This is the second article in a two-part series that aims to describe the principles of investigating and treating common back pathologies in riding horses. The first article (Findley and others 2015) discussed the various diagnostic techniques available to aid the clinician in diagnosing back pain of the thoracolumbar and sacroiliac regions. The strengths and limitations associated with each technique and the challenges involved with reaching a specific diagnosis were outlined. This second article focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The numerous studies evaluating the accuracy of US-guided injections in the axial and sacroiliac region compared to “blind techniques” could have helped the diffusion in clinical settings [ 34 , 36 38 ]. Although there is limited evidence of its effectiveness [ 32 , 33 ], mesotherapy was perceived as a therapy with good efficacy between respondents to our last survey. The topical administration was the prevailing route for drugs administration in the 2016' survey because perceived as more effective.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The numerous studies evaluating the accuracy of US-guided injections in the axial and sacroiliac region compared to “blind techniques” could have helped the diffusion in clinical settings [ 34 , 36 38 ]. Although there is limited evidence of its effectiveness [ 32 , 33 ], mesotherapy was perceived as a therapy with good efficacy between respondents to our last survey. The topical administration was the prevailing route for drugs administration in the 2016' survey because perceived as more effective.…”
Section: Discussionmentioning
confidence: 90%
“…The two surveys confirmed that corticosteroids are the main drug family used by the interviewed veterinarians to treat back disorders. Interestingly, the use of a distillate of powdered of pitchered plant (Sarracenia purpurin) as an analgesic agent is still widespread, although its efficacy with regard to horses is not documented in literature [ 33 ]. This data is surprising also considering the limited availability of the corresponding commercial preparations (Sarapin®, P-Block®) in most European countries and the counterproductive effect that could have in mesotherapy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different techniques for subtotal ostectomy have been described. An open method can be achieved both under general anaesthesia or in a standing position with the help of sedation and local anaesthesia techniques 15,23–27 . As described by Perkins et al., this procedure is associated with less haemorrhage as well as fewer anaesthetic and sedation‐related complications 27 .…”
Section: Discussionmentioning
confidence: 99%
“…While recognising the placebo effect, in general terms an improvement in performance usually does indicate a pain‐related problem. A failure to observe improvement does not preclude pain: some causes of pain, for example sacroiliac joint region pain, may be unaffected (Findley and Singer 2016). However, in our case series three out of four horses which were administered phenylbutazone were reported by owners to have no change in headtossing behaviour, which is potentially confusing.…”
Section: Discussionmentioning
confidence: 99%